Fatty acid export (FAX) proteins contribute to oil production in the green microalga Chlamydomonas reinhardtii - Peter, Janick; Huleux, Marie; Spaniol, Benjamin; Sommer, Frederik; Neunzig, Jens; Schroda, Michael; Li-Beisson, Yonghua; Philippar, Katrin (Frontiers in Molecular Biosciences, 2022)
In algae and land plants, transport of fatty acids (FAs) from their site of synthesis in the plastid stroma to the endoplasmic reticulum (ER) for assembly into acyl lipids is crucial for cellular lipid homeostasis, including the biosynthesis of triacylglycerol (TAG) for energy storage. In the unicellular green alga Chlamydomonas reinhardtii, understanding and engineering of these processes is of particular interest for microalga-based biofuel and biomaterial production. Whereas in the model plant Arabidopsis thaliana, FAX (fatty acid export) proteins have been associated with a function in plastid FA-export and hence TAG synthesis in the ER, the knowledge on the function and subcellular localization of this protein family in Chlamydomonas is still scarce. Among the four FAX proteins encoded in the Chlamydomonas genome, we found Cr-FAX1 and Cr-FAX5 to be involved in TAG production by functioning in chloroplast and ER membranes, respectively. By in situ immunolocalization, we show that Cr-FAX1 inserts into the chloroplast envelope, while Cr-FAX5 is located in ER membranes. Severe reduction of Cr-FAX1 or Cr-FAX5 proteins by an artificial microRNA approach results in a strong decrease of the TAG content in the mutant strains. Further, overexpression of chloroplast Cr-FAX1, but not of ER-intrinsic Cr-FAX5, doubled the content of TAG in Chlamydomonas cells. We therefore propose that Cr-FAX1 in chloroplast envelopes and Cr-FAX5 in ER membranes represent a basic set of FAX proteins to ensure shuttling of FAs from chloroplasts to the ER and are crucial for oil production in Chlamydomonas.